ประสิทธิภาพบทเรียนคอมพิวเตอร์ช่วยสอนแบบสถานการณ์จำลองบนเครือข่ายอินเทอร์เน็ต เรื่อง แนวปฏิบัติการป้องกันการติดเชื้อในโรงพยาบาล สำหรับนักศึกษาพยาบาล - ไชยมณี, ธิดาวรรณ; ดิสถาพร, ชไมพร; โรจน์สัมฤทธิ์, วัฒนีย์; อ่อนมิ่ง, ฤทธิชัย (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 28 No 1 (2560): Academic Services Journal, Prince of Songkla University, 2017)
วัตถุประสงค์: 1) เพื่อพัฒนาบทเรียนคอมพิวเตอร์ช่วยสอนแบบสถานการณ์จำลองบนเครือข่ายอินเทอร์เน็ต เรื่อง แนวปฏิบัติการป้องกันการติดเชื้อในโรงพยาบาล สำหรับนักศึกษาพยาบาล 2) เพื่อศึกษาประสิทธิภาพบทเรียนคอมพิวเตอร์ช่วยสอนแบบสถานการณ์จำลองบนเครือข่ายอินเทอร์เน็ตที่สร้างขึ้น วิธีการดำเนินการวิจัย: เป็นการวิจัยกึ่งทดลอง กลุ่มตัวอย่างเป็นนักศึกษาพยาบาล ชั้นปี 2 วิทยาลัยพยาบาลบรมราชชนนี กรุงเทพ จำนวน 48 คน เลือกด้วยวิธีการสุ่มอย่างง่าย เครื่องมือที่ใช้ในการวิจัย ได้แก่ 1) แบบสอบถามความต้องการลักษณะบทเรียนคอมพิวเตอร์ช่วยสอนฯ 2) แบบประเมินความเหมาะสมบทเรียนคอมพิวเตอร์ช่วยสอนฯ 3) แบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน เรื่องแนวปฏิบัติการป้องกันการติดเชื้อในโรงพยาบาล ขั้นตอนการพัฒนาบทเรียนคอมพิวเตอร์ช่วยสอนฯ แบ่งเป็น 4 ขั้นตอน คือ ขั้นตอนที่ 1 การศึกษาข้อมูลพื้นฐานและความต้องการลักษณะบทเรียนคอมพิวเตอร์ช่วยสอนฯ ขั้นตอนที่ 2 การออกแบบบทเรียนคอมพิวเตอร์ช่วยสอนฯ ขั้นตอนที่ 3 การพัฒนาบทเรียนคอมพิวเตอร์ช่วยสอนฯ ขั้นตอนที่ 4 การทดสอบประสิทธิภาพบทเรียนคอมพิวเตอร์ช่วยสอนฯ วิเคราะห์ข้อมูลโดยใช้สถิติ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และสถิติที่ใช้ในการหาประสิทธิภาพบทเรียนคอมพิวเตอร์ช่วยสอน ได้แก่ E1/E2 ผลการวิจัย: 1) บทเรียนคอมพิวเตอร์ช่วยสอนแบบสถานการณ์จำลองบนเครือข่ายอินเทอร์เน็ต เรื่อง แนวปฏิบัติการป้องกันการติดเชื้อในโรงพยาบาล มีการนำเสนอบทเรียนในเมนูหลักออกเป็น 6 ส่วน ได้แก่ คำชี้แจงบทเรียน แบบทดสอบก่อนเรียน การทบทวนบทเรียน การเล่นสถานการณ์จำลอง การทดสอบหลังเรียน และการติดต่อสื่อสารระหว่างผู้เรียนกับผู้สอน มีลักษณะเป็นการจำลองเหตุการณ์เกี่ยวกับพยาบาลทำกิจกรรมการพยาบาลให้ผู้ป่วยข้างเตียงในหอผู้ป่วย และให้นักศึกษาพยาบาลตอบคำถามเกี่ยวกับวิธีการป้องกันการติดเชื้อในโรงพยาบาลที่ถูกต้องเหมาะสมแต่ละกิจกรรมการพยาบาลเกี่ยวกับ การล้างมือ การใช้เครื่องป้องกันร่างกาย การป้องกันอุบัติเหตุของมีคม และการแยกทิ้งมูลฝอยในโรงพยาบาล มีกรณีศึกษาแบ่งเป็น 3 โจทย์สถานการณ์ คือ ผู้ป่วยโรคอุจจาระร่วง ผู้ป่วยติดเชื้อทางเดินปัสสาวะ และผู้ป่วยที่เป็นวัณโรคปอด 2) ผลการหาประสิทธิภาพของบทเรียนคอมพิวเตอร์ช่วยสอนแบบสถานการณ์จำลองบนเครือข่ายอินเทอร์เน็ตเรื่อง แนวปฏิบัติการป้องกันการติดเชื้อในโรงพยาบาล มีประสิทธิภาพเท่ากับ 88.44/87.33 เป็นไปตามเกณฑ์ที่กำหนดไว้ 85/85 สรุป: บทเรียนคอมพิวเตอร์ช่วยสอนแบบสถานการณ์จำลอง สื่อการสอนมีลักษณะสร้างเหตุการณ์หรือสถานการณ์จำลอง เพื่อฝึกคิดควบคุมเหตุการณ์ การตัดสินใจ พัฒนาผลสัมฤทธิ์ทางการเรียนทั้งด้านความรู้และทักษะความสามารถในการปฏิบัติพยาบาลของนักศึกษา คำสำคัญ: คอมพิวเตอร์ช่วยสอนแบบสถานการณ์จำลอง, แนวปฏิบัติการป้องกันการติดเชื้อในโรงพยาบาล, นักศึกษาพยาบาล   Objective: To develop an internet-based computer based simulation on practice guidelines for preventing nosocomial infections with efficiency meeting the 85/85 criteria. Materials and methods: This study was based on a quasi-experimental research design. The sample group recruited for the present study was made up of forty eight nursing students at Boromarajonani College of Nursing Bangkok who were divided to determine the efficiency of the internet-based CAI simulation. The instrumentation was composed of the following: 1) the computer-based simulation needs questionnaire; 2) the computer simulation suitability assessment form and 3) the form for testing learning achievement on practice guidelines for the prevention of infections in hospitals. The procedures for developing the computer simulation were divided into the following four steps: Step 1 Study preliminary data and computer-based simulation needs; Step 2 Design computer-based simulations; Step 3 Develop computer-based simulations and Step 4 Test computer-based simulation efficiency. The data were analyzed by determining percentage, mean and standard deviation to find the efficiency of the internet-based CAI simulation was E1/E2. Results: The research findings can be summarized as follows: 1) The online computer-based simulation on practice guidelines for the prevention of infections in hospitals presented lessons divided into six parts in the main menu, namely, lesson explanations, test forms before learning, lesson reviews, simulations, post-learning tests and student-teacher communication. Simulations involved the performance of bedside care activities by nurses for patients in a patient ward. Nursing students answered questions about accurate and suitable methods for preventing nosocomial infections in hospitals. Each care activity involved hand washing, the use of personal protection equipment, prevention of accidents from sharp objects and waste sorting in hospitals. Case studies were divided into three questioning situations consisting of patients with diarrhea, patients with urinary infections and patients with tuberculosis, 2) According to the findings, the efficiency of the internet-based CAI simulation on preventive guidelines against nosocomial infections in hospitals was 88.44/87.33 for the nursing students, which was higher than the standard 85/85 criteria. Conclusion: Computer-assisted instruction (CAI) simulation teaching media creates a simulated event or situation aimed at practicing situational control, decisions to develop learning capacity in terms of knowledge, skills and ability in the nursing practice of nursing students. Keywords: computer based simulation, practice guidelines prevention of nosocomial infection, nursing students